The Influence of The Sabo Dam Bronggang on Disaster Mitigationpublic About The Danger of Merapi Mountain Eruption - Wahyu Gerhana, Sony Eka; Nugroho Hari Purnomo; Muhammad Asyroful Mujib; Moch. Shofwan; Hanifah Mahat (International Journal of Geography, Social, and Multicultural Education, 2023)
Mount Merapi In 2010 was the biggest eruption that ever happened to Mount Merapi. Judging from the number of fatalities in this eruption, it reached 277 people and material losses were estimated at 4.5 trillion which resulted in the cessation of access to transportation links. This study aims to determine the impact felt by the community on the construction of the Sabo Bronggang Dam. This study used a descriptive qualitative method with data collection techniques using interviews, observation and documentation. Interviews were conducted by asking the surrounding community about the Sabo Bronggang Dam for the construction of the dam, then comparing before and after the existence of this dam, how was the impact felt, was it effective in dealing with cold lava floods, and whether there is any effectiveness in overcoming cold lava floods, and whether there are any additional developments to provide a sense of security in the awareness of disaster mitigation efforts. From the results of the study, it was stated that the surrounding community felt safe when at any time there was another eruption of the Sabo Bronggang Dam, besides that it could also be used as an attractive destination to visit because of its natural beauty